2010
DOI: 10.1002/jat.1493
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450‐dependent toxicity of dapsone in human erythrocytes

Abstract: The most prominent adverse effects seen during treatment with dapsone, an antibacterial and antiprotozoal agent, are hemolysis and methemoglobinemia. An in vitro microsomal/cytochrome P(450) (CYP)-linked assay, which allows reactive metabolites generated in situ to react with the co-incubated human erythrocytes, was employed to profile CYP isoforms responsible for hemotoxicity of dapsone. Dapsone caused a robust generation of methemoglobin in human erythrocytes in the presence of human/mouse liver microsomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Methemoglobinemia is reported to be induced by certain types of clinically used drugs, including the analgesic antipyretic phenacetin, the antileprosy drug dapsone, and the antibiotic sulfamethoxazole (Reilly et al, 1999;Ganesan et al, 2010;Kobayashi et al, 2012), which all possess an aromatic amine moiety. N-Hydroxylamines, which are Nhydroxylated metabolites of aromatic amines, were suspected to be a cause of aromatic amine-induced methemoglobinemia (Spooren and Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methemoglobinemia is reported to be induced by certain types of clinically used drugs, including the analgesic antipyretic phenacetin, the antileprosy drug dapsone, and the antibiotic sulfamethoxazole (Reilly et al, 1999;Ganesan et al, 2010;Kobayashi et al, 2012), which all possess an aromatic amine moiety. N-Hydroxylamines, which are Nhydroxylated metabolites of aromatic amines, were suspected to be a cause of aromatic amine-induced methemoglobinemia (Spooren and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is conceivable that CES1A, CES2, and AADAC are involved in the hydrolysis of prilocaine and lidocaine. Ganesan et al (2010) reported that dapsone-hydroxylamine, which is an N-hydroxylated metabolite of dapsone, was suspected to be a cause of dapsone-induced methemoglobinemia. The formation of dapsonehydroxylamine is catalyzed by cytochromes P450 (P450) CYP2C19, CYP2E1, and CYP3A4.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the role of the hydroxylamine metabolites in dapsone toxicity is well established, the CYP isoforms primarily responsible for their formation have been the subject of considerable study in a variety of clinical and experimental models over past decades; indeed, CYP3A4, CYP2E1 and CYP2C9 [11]–[13] have each been postulated as the major contributor to the oxidation of this drug. Latterly, a role for CYP2C19, has been outlined in a study with recombinant isoforms [14] and in our report we also explore the potential interactions between dapsone and CYP2C19 using molecular docking analysis.…”
Section: Introductionmentioning
confidence: 91%
“…Despite encouraging in vitro evidence [24], N-acetylcysteine had no significant effect on nitrate-induced methemoglobinemia in two small human controlled trials [25,26]. The theoretical potential of cytochrome P450 (CYP450) inhibitors such as cimetidine is limited to methemoglobinemia induced by drugs such as dapsone and sulfasalazine, which are converted into their oxidant forms by CYP450 enzymes [27,28]. There are no reports of CYP450 inhibitor therapy in acute methemoglobinemia [29].…”
Section: Discussionmentioning
confidence: 99%